IoT and AI-Driven Audio in the Smart City: A Rhythmanalysis inspired approach - Roddy, Stephen (My University, 2018)
French Philosopher and theorist Henri Lefebvre's The Production of Space (1991) has proved a crucial text for framing the discourse around contemporary urban society in the fields of human geography, critical theory, cultural studies and sound studies. With the recent wave of research focusing on the Internet of Things, the Smart City and complementary developments in the research and application of geolocative technologies another of Lefebvre's works, his posthumous collection of essays on the concept of Rhythmanalysis (2004), has increasingly come to the fore (Coletta and Kitchin, 2017).
The Irish Sound Science and Technology Association Conference